2000
DOI: 10.3923/pjbs.2000.1161.1163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Salinity Levels on the Yield and Yield Components of Wheat Cultivars

Abstract: Statistical analysis of the data revealed that yield and yield components of Wheat cultivars were significantly (p<0.05) affected by different salinity levels. Agronomic characters i.e. plant height, tillers plantG 1 , number of grains plantG 1 , 100 grains weight, grain and straw yield and harvest index of two salt tolerant cultivars (Mutant and Lu 26S) were reduced less than salt sensitive cultivars (Yecora and WS 711). Mutant and Lu 268 proved more salt tolerant than other cultivars at all growth stages. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…Shoot length was reduced in water stress regimes; it might be because of the difference in genetic makeup of both varieties along with insufficient availability of essential nutrients under water-stress. These outcomes are in conformity with the findings of Sarwar et al (2010) stating significant relationship between varieties and levels of irrigation. Application of FYM increased shoot length of wheat (Sharma et al 2005).…”
Section: Discussionsupporting
confidence: 91%
“…Shoot length was reduced in water stress regimes; it might be because of the difference in genetic makeup of both varieties along with insufficient availability of essential nutrients under water-stress. These outcomes are in conformity with the findings of Sarwar et al (2010) stating significant relationship between varieties and levels of irrigation. Application of FYM increased shoot length of wheat (Sharma et al 2005).…”
Section: Discussionsupporting
confidence: 91%
“…Irrigation at critical stages resulted in highest seed yield in rice whereas yield of wheat was highest with irrigation at 1.0 CPE. These results are in line with findings of Sarwar et al, (2010). The high seed yield of rice in inorganic management in the first year may be owing to the fact that inorganic fertilizers release nutrients instantly and in readily available forms for the plants during its growth, development and reproductive phase when the nutrient demand is at its peak.…”
Section: Yieldsupporting
confidence: 90%
“…The differences in days to heading among genotypes across environments were due to genetic variability and the environment has no influence on genotypes performance. Results of this study were supported by [9,11] also reported significant differences for days to heading, while non-significant interaction results validated the findings of [9,8]. The correlation results were supported by the finding of [12], who investigated a non-significant positive correlation between days to heading and grains spike -1 , a non-significant negative correlation between days to heading and plant height, while in contrast to the present results a positive and significant correlation between days to heading and spike length.…”
Section: Days To Headingsupporting
confidence: 80%
“…Soil moisture not only affects physiochemical activities of a plant but also regulates the translocation of plant nutrients to various organs. Hence, adequate and timely irrigation is one of the most important cultural practices that should be considered necessary for successful crop husbandry [8]. The screening of elite and exotic wheat germplasm for drought tolerance is desirable to boost up grain yield [9].…”
Section: Introductionmentioning
confidence: 99%